2021
DOI: 10.1177/2324709621997282
|View full text |Cite
|
Sign up to set email alerts
|

An Uncommon Presentation of DRESS Syndrome Secondary to Leflunomide Use: A Case Report

Abstract: Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a constellation of symptoms that manifest as a result of certain medications. Several antipsychotics, antibiotics, and sulfa-containing drugs are known to be implicated in the etiology of DRESS syndrome. The clinical presentation of this disorder consists of a diffuse rash, lymphadenopathy, and systemic organ damage. Our patient presented with symptoms consistent with DRESS syndrome after being started on leflunomide, which is not common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…It is a systemic, severe drug hypersensitivity syndrome, typically encountered in adults but is uncommon in children. [2,7]. According to the RegiSCAR scoring system, which categorizes DRESS Syndrome as "excluded," "possible," "probable," or "definite" and on this basis the diagnosis of the patient is made 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a systemic, severe drug hypersensitivity syndrome, typically encountered in adults but is uncommon in children. [2,7]. According to the RegiSCAR scoring system, which categorizes DRESS Syndrome as "excluded," "possible," "probable," or "definite" and on this basis the diagnosis of the patient is made 3.…”
Section: Discussionmentioning
confidence: 99%
“…DRESS syndrome has been linked to antiepileptic drugs such as phenytoin, lamotrigine and carbamazepine. Antibiotics that contain sulfa, minocycline, and vancomycin have also been linked to this syndrome [7]. Kawasaki disease is the second most common cause of vasculitis in children after Henoch Schonlein purpura like DRESS Syndrome [8].…”
Section: Introductionmentioning
confidence: 99%
“…While gastrointestinal events such as nausea and diarrhea are the most reported adverse effects of LEF therapy [7], DRESS syndrome is rarely reported. A literature review of PubMed revealed only nine previous cases of LEF-induced DRESS syndrome have been reported [8][9][10][11][12], suggesting that the rate of LEF-induced DRESS syndrome is significantly less than the average incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome, is a rare and potentially life-threatening multiorgan system reaction with a constellation of symptoms such as rash, fever, swelling, lymphadenopathy, leukocytosis and eosinophilia,with the most distinct feature being end organ dysfunction. [1][2][3] The incidence of DRESS syndrome in new users is approximately 1 per 1500 and has a mortality rate of 10%. 4 The most frequent culprit drugs are anticonvulsants (phenytoin, phenobarbital), allopurinol and sulfonamides, with a long prodromal period of 2 to 6 weeks.…”
Section: Introductionmentioning
confidence: 99%